2006
DOI: 10.1136/jnnp.2005.066134
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve and spinal cord manifestations of malignant atrophic papulosis (Degos disease)

Abstract: A fatal case of malignant atrophic papulosis (Degos disease) with optic nerve and spinal cord involvement is described. Magnetic resonance imaging (MRI) of the optic nerve showed abnormal signal enhancement on fat suppressed T1 weighted images after intravenous meglumine gadopentetate infusion. On T2 weighted sagittal images, a sawtooth pattern was observed over seven vertebral segments of the spinal cord. On necropsy, a severe loss of myelinated nerve fibres in the left optic nerve was seen, with thrombotic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Other successful strategies include administration of tripterygium wilfordii polyglycosidium, folic acid, vitamin B 12 , and thymopeptide; however, the use of steroids should be avoided because previous studies have not shown any success with steroid treatment regimens, and steroids can increase the risk of intestinal perforation 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other successful strategies include administration of tripterygium wilfordii polyglycosidium, folic acid, vitamin B 12 , and thymopeptide; however, the use of steroids should be avoided because previous studies have not shown any success with steroid treatment regimens, and steroids can increase the risk of intestinal perforation 7 …”
Section: Discussionmentioning
confidence: 99%
“…Other successful strategies include administration of tripterygium wilfordii polyglycosidium, folic acid, vita-min B12, and thymopeptide; however, the use of steroids should be avoided because previous studies have not shown any success with steroid treatment regimens, and steroids can increase the risk of intestinal perforation. 7 In summary, discovering a definitive diagnosis and effective treatment for Degos disease remains a challenge. Although Degos disease does not present with a distinct clinical entity, the unique skin lesions and histological findings can be helpful in its diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“… 5 - 7 In addition, some other ophthalmic signs have been reported in MAP, including conjunctival atrophic plaques, telangiectatic vessels, scleral thinning, blepharoptosis and optic atrophy. 6 , 8 Secondly, she repeatedly felt numbness in her right calf. EMG showed right quadriceps femoris neurogenic damage, which suggested the patient also had peripheral nerve involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the pathology of CNS involvement in a patient with MAP includes disseminated occlusive vasculopathy and the resulting diffuse ischemic changes 2 . About 75% of the patients are male and the disease is most frequently in the third and fourth decades of life 5 .…”
Section: Discussionmentioning
confidence: 99%
“…This rare disorder is an obstructive vasculopathy of unknown origin, characterized by vascular lesions of the skin, central nervous system (CNS) and gastrointestinal tract 1 . Skin lesions are usually the first manifestation of the disease, although the poor prognosis is resultant of the gastrointestinal and CNS involvement 2 . Once multisystemic disease has developed, death occurs in approximately 50% of patients within 1 to 2 years, mostly due to intestinal perforation or, less commonly, cerebral infarctions 3 .…”
mentioning
confidence: 99%